KAJI EKSPERIMENTAL PANAS KONDENSOR AC SPLIT DENGAN VARIASI PUTARAN FAN UNTUK PENGERINGAN PADI - yudhy kurniawan; Kusnandar Kusnandar; Yusup Nur Rohmat; wardika wardika (Jurnal Teknologi Terapan, 2020)
The use of Split of Air Conditioning (AC) which is usually used for air conditioning for human convenience. In this study a split AC was used for drying rice. Rice drying using Split AC is a type of artificial drying that has an advantage compared to natural, which is shorter drying. In Split AC the hot air generated from the condenser released into the environment is useless will be flowed through the air duct to be used for drying rice. The use of condenser heat is carried out to find out how to grow rice by using variations in the condenser fan speed regulation. In Split AC, it is done to find out the flow of drying with a variation fan rotation speed of 450 rpm and 800 rpm. From the results of the data experiment for taking around 1.5 hours in the drying process obtained moisture content is 8% and 12% for the 450 rpm and 800 rpm condenser fan rotation each. Although the temperature of the air produced by the condenser heat is 53.6 oC and 50.6oC. The other data of relative humidity of the air (Relative Humidity) is 15%.